1998
DOI: 10.1089/acm.1998.4.3-289
|View full text |Cite
|
Sign up to set email alerts
|

The Scientific Rediscovery of an Ancient Chinese Herbal Medicine: Cordyceps sinensis Part I

Abstract: This review presents Cordyceps sinensis (Berk.) Sacc., a fungus highly valued in China as a tonic food and herbal medicine. The extant records show the continued use of C. sinensis is now centuries old. The major chemical, pharmacological, and toxicological studies on C. sinensis and the various derived, cultured, fermented mycelial products currently in use are reviewed from the English and Chinese literature. Preclinical in vitro and in vivo studies and clinical blinded or open-label trials in to date over 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
270
1
4

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 452 publications
(288 citation statements)
references
References 3 publications
2
270
1
4
Order By: Relevance
“…C. militaris contains many active components, such as cordycepin, polysaccharide, cordycepic acid, amino acids, trace elements, and other chemical compositions [Fan and Lin 2013;Ni et al 2007]. Traditional Chinese medicine believes that C. militaris can be used to treat impotence, seminal emission, and infertility, and invigorate kidney and lungs [Ch 2000;Zhu et al 1998]. Pharmacological studies have confirmed that C. militaris possesses a wide range of biological activities including anti-bacterial, anti-tumor, anti-oxidation, and immune-modulatory [Liu et al 1994;Ng and Wang 2005;Reis et al 2013].…”
Section: Introductionmentioning
confidence: 99%
“…C. militaris contains many active components, such as cordycepin, polysaccharide, cordycepic acid, amino acids, trace elements, and other chemical compositions [Fan and Lin 2013;Ni et al 2007]. Traditional Chinese medicine believes that C. militaris can be used to treat impotence, seminal emission, and infertility, and invigorate kidney and lungs [Ch 2000;Zhu et al 1998]. Pharmacological studies have confirmed that C. militaris possesses a wide range of biological activities including anti-bacterial, anti-tumor, anti-oxidation, and immune-modulatory [Liu et al 1994;Ng and Wang 2005;Reis et al 2013].…”
Section: Introductionmentioning
confidence: 99%
“…Chinese cordyceps is one of the best known traditional Chinese medicines, endemic to alpine regions of the Tibetan Plateau and is thought to have been discovered 2000 years ago (Zhu et al 1998). It was officially documented for medicinal uses in the Qing dynasty (Wang 1694; Zhao 1765) to replenish the kidney and soothe the lung and was officially classified as a drug in the Chinese Pharmacopeia in 1964 (Committee of Pharmacopeia, Chinese Ministry of Health 1964).…”
Section: The Chinese Cordyceps Industrymentioning
confidence: 99%
“…Many natural cordyceps are used in traditional Chinese medicines in China, Japan, Korea and other eastern Asian countries (Zhu et al 1998). Of the different varieties of cordyceps fungi, those presently being developed for medicinal purposes, health supplements and pharmaceutical drugs in China include but not limited to O. sinensis (Berk.)…”
Section: Introductionmentioning
confidence: 99%
“…It is generally used to nourish the kidney, moisten the lung, fight fatigue and enhance immunity [8]. Furthermore, the wild O. sinensis is exiguity and expensive in the market, so the mycelia fermentation has become to an economical method to meet large requirement of the market [5].…”
Section: O Sinensis Called Cordyceps or Dong Chong Xia Cao In Chinamentioning
confidence: 99%